A sustainability transition on the move? Evidence based on the disconnect from market fundamentals - Lucia Alessi; Dominik Hirschbühl; Alessandro Rossi (European Commission, 2022)
In a context where European stock prices have been trending upwards, one of the main concerns is that stocks perceived as more sustainable from an environmental, social and governance (ESG) perspective could be particularly exposed to exuberance. To shed some light on the magnitude of the deviation of stock prices from fundamentals we apply a Markov-switching augmented version of the present-value model. Using monthly data on the European stock market from 2005 to 2022, our model suggests that at the beginning of 2022 the non-fundamental component was about one fourth of the total price. When looking at particular market segments, the model shows that green and ESG stocks behave broadly in line with the market. However, in recent years ESG stocks have shown a significant, though small, disconnect from the market. These findings suggest that investor preferences are shifting towards sustainability, while not posing immediate risks to market stability.
Keywords: C11; C32; G12; 330; Bayesian inference; European stock market; green transition; Markov-switching; present-value model